2004
DOI: 10.1016/j.femsre.2003.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Quorum sensing and swarming migration in bacteria

Abstract: Bacterial cells can produce and sense signal molecules, allowing the whole population to initiate a concerted action once a critical concentration (corresponding to a particular population density) of the signal has been reached, a phenomenon known as quorum sensing. One of the possible quorum sensing-regulated phenotypes is swarming, a flagella-driven movement of differentiated swarmer cells (hyperflagellated, elongated, multinucleated) by which bacteria can spread as a biofilm over a surface. The glycolipid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
377
0
14

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 532 publications
(399 citation statements)
references
References 234 publications
(465 reference statements)
8
377
0
14
Order By: Relevance
“…The results demonstrated that genes for iron metabolism were strongly induced in bacteria grown on swarming agar plates with less-nutritional conditions. It was reported that excess iron prevents swarming motility, and less-nutritional conditions may induce swarming and biosurfactant production in P. aeruginosa (7). From these reports, a reduced ability to acquire iron may relate to the hyperswarming motility in the ⌬orf3 mutant.…”
Section: Vol 188 2006mentioning
confidence: 99%
See 2 more Smart Citations
“…The results demonstrated that genes for iron metabolism were strongly induced in bacteria grown on swarming agar plates with less-nutritional conditions. It was reported that excess iron prevents swarming motility, and less-nutritional conditions may induce swarming and biosurfactant production in P. aeruginosa (7). From these reports, a reduced ability to acquire iron may relate to the hyperswarming motility in the ⌬orf3 mutant.…”
Section: Vol 188 2006mentioning
confidence: 99%
“…EPS production and tolerance to H 2 O 2 and antibiotics. Previous papers have reported that the production of EPS is regulated by quorum sensing and that an EPS-deficient mutant of P. syringae is hypersensitive to environmental stresses (7,17,25). To compare extracellular polysaccharide production on an MMMF plate with 1.5% agar after 48 h of incubation at 27°C, each mutant was scraped off and the amounts of extracellular polysaccharide and extracellular proteins as an internal control were quantified (Fig.…”
Section: Detection Of Ahls and Northern Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, AMF as well as quantities of other microbes also exist in the rhizosphere, such as P-solubilizing bacteria and mycorrhizal-helping bacteria (MHB) initiate a concerted action when a particular population density is achieved, i.e., quorum sensing (Khan, 2005). This phenomenon expands the environmental signals to a larger range (Daniels et al, 2004). The involvement of fungi is beyond the scope in our review and will not be further discussed.…”
Section: Endophytic Effects and Concerted Actionmentioning
confidence: 99%
“…Acylhomoserine lactones in Gram-negative bacteria as well as indole, and autoinducer 2 in both Gram-negative and Grampositive bacteria (Jayaraman and Wood, 2008;Han et al, 2010) are typical QS signals. QS regulates swarming motility (Daniels et al, 2004).…”
Section: Introductionmentioning
confidence: 99%